أثر الثقافة التنظيمية على زيادة أداء الموظفين في المنظمات الخدمية: كلية طب الأسنان خليج ليبيا - جامعة طرابلس الأهلية: حالة دراسية - الخوجة، نجاة صبحي (مركز البحث وتطوير الموارد البشرية - رماح, 2024)
هدفت الدراسة إلى التعرف على أثر الثقافة التنظيمية على زيادة الأداء الوظيفي. ولتحقيق ذلك أجريت الدراسة على 18 موظف بكلية طب الأسنان/ خليج ليبيا إذ تكون مجتمع الدراسة من الموظفين بالكلية. وقد تم اختيار عينة الدراسة بطريقة المسح الشامل للموظفين الإداريين فقط، حيث تم توزيع (18) استمارة استبيان، استعيدت (18) استمارة بالكامل صالحة للتحليل. وعند تحليل البيانات باستخدام برنامج SPSS، أظهرت النتائج أن مستوى الثقافة التنظيمية في الكلية المعنية كان على درجة كبيرة.. كما أظهرت نتائج الدراسة أن جميع أبعاد الثقافة التنظيمية لها أثر ذو دلالة إحصائية على الأداء الوظيفي للعاملين، وأن تأثير أبعادها متباينا. The study aimed to identify the impact of organizational culture on increasing job performance. To achieve this, the study was conducted on 18 employees of the Faculty of Dentistry/ Gulf of Libya, as the study population consisted of the faculty. The study sample was selected using the comprehensive survey method for administrative staff only, where (18) questionnaires were distributed, and (18) questionnaires were fully recovered, and valid for analysis. When analyzing the data using the SPSS program, the results showed that the level of organizational culture in the concerned college was to a large degree.. The results of the study also showed that all dimensions of organizational culture had a statistically significant impact on the job performance of employees and that the impact of its dimensions varied.
Keywords: المنظمات الخدمية -- الثقافة الوطنية -- البناء التنظيمي